Why does critical literacy hit a snag in the iranian EFL setting? - Rahimi, Ali; Askari Bigdeli, Rouhollah (Colombian Applied Linguistics Journal, 2015)
This study sought to elucidate the challenges of critical literacy practice in the Iranian context. The objectives were twofold: (a) to find out which challenges teachers and students face in the practice of critical literacy and (b) to explore the state of critical literacy in language education. To this end, a sample of 12 English teachers and 120 students majoring in TEFL took part in the study. Data collection procedure was based on students’ reflective notes, semi-structured interviews, and classroom observations. The analysis of the interviews revealed that factors including a) lack of the teachers’ familiarity with the concept and tenets of critical literacy, b) students’ poor English proficiency, c) lack of attention to critical literacy in curriculum and d) political issues were the major challenges. Classroom observations and students’ reflective notes showed that teachers did not encourage students to become involved in ideologies imbedded in the texts.